Spatial mobility of the employed population and occupational structure of the labour force in industry of the Tuzla valley - Nurković, Rahman (Journal for Geography, 2007)
The objective of this paper is to show, to a certain extent, daily migrations of labour force in industry of the Tuzla valley. In addition to Tuzla, the three centres are distinguished according to importance of their function of work: Lukavac, Živinice and Banovići. On one hand, we have a strong concentration of industrial jobs, and on the other, almost unindustrialised remaining territory.